Urban Fringe Development Planning: Strategic Interventions to Balance Industrial Growth, Ecological Preservation, and Community Livability - Kotalkar, Krishna Panchal (Journal of Progress in Civil Engineering, 2025)
Urbanization has caused the development of residential, commercial and industrial developments beyond the municipal limits of the city, leading to a haphazard development. This has caused the transformation of villages from rural to urban, giving them mixed characteristics of village and city. Trivandrum corporation, being the most highly populated corporation in Kerala, is under constant pressure for development, especially with the technocentric and industrial developments at Kazhakkoottam in its periphery showing a ribbon development which is the most typical form of chaotic fringes in India. The paper aims to provide the recommendations for the development of Kazhakkoottam urban fringe through spatial analysis of land use and infrastructural facilities in the area.